Factors influencing Malaysian pineapple smallholders intention to adopt MyGAP and MPIB roles to inspire the growers to obtain MyGAP certification - Fam, Soo-Fen; Jamaliah, Laham; Zaiton, Sapak; Chuan, Zun Liang; Amiruddin, Ahamat; Wan Zawaiah, Wan Zin; Suhartono, . (Fakulti Pengajian Peradaban Islam, Kolej Universiti Islam Antarabangsa Selangor, 2019)
Purpose of the study: The study aims to identify the factors influencing growers‟ intention to adopt MyGAP and MPIB roles and to inspire the pineapple growers to obtain MyGAP certificate.